Thailand : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses selected issues related to the economy of Thailand. The economy of Thailand is largely dependent on China. A 1 percent decline in China's GDP lowers Thailand's output by about 0.2 percent. Population aging is another major issue in Thailand. This Association of Southeast Asian Nations country will face the dual challenge of increasing the coverage of the social security system and ensuring its long-term sustainability. Thailand's financial sector has expanded rapidly over the last decade, and important changes in its structure have taken place. While corporate debt has remained broadly stable, household debt has increased to one of the highest levels among emerging markets, raising concerns about household debt overhang.